The Prevalence of Lower Urinary Tract symptoms (LUTS) and incontinence in Iranian Women - Zargham, Mahtab; Pourmomeny, Abbas Ali; Soltanmohamadi, Mahsa (Urology Journal, 2020)
Purpose: Lower Urinary Tract Symptoms (LUTS) affect many women worldwide. The prevalence of LUTS among Iranian women has not been reported. The aim of the present study was to evaluate the prevalence of Lower Urinary Tract Symptoms and its bother rate among women ?20 years old living in Isfahan, a central province of Iran. Materials and Methods: This was a descriptive cross-sectional study. The data was collected using a population-based survey on women aged ?20 years selected from the general population of Isfahan (a central province of Iran. A total of 2609 women were approached for the study. After obtaining demographic features, the participants completed the Persian version of the International Consultation on Incontinence Modular Questionnaire for Female Lower Urinary Tract Symptoms (ICIQ-FLUTS). Results: 95.5% of the participants had at least one Lower Urinary Tract Symptoms. The most common symptoms were urgency (82.4%) and stress urinary incontinence (44.5%). Nocturia (one or more occasions) was also noted in 60.7%. The highest bother rate was related to urgency. Conclusion: The prevalence of Lower Urinary Tract Symptoms was high in the studied women. Among Lower Urinary Tract Symptoms, urgency and nocturnal enuresis were the most and the least frequent symptoms. However, the bother rate of the symptoms was relatively low.